Implications of work motivation, employee discipline, and compensation on employee performance while working from home at a digital marketing company - Ahmad Azmy; Handi Risza; Arief Adhykusuma (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
Many organizations apply WFH policy during the pandemic. In this study, we focused on the employee performance quality when engaged in this working pattern. The result of the study is expected to provide positive recommendations to organizations in implementing the WFH policy. This approach allows researchers to see the significance of the construct and its effect on employee performance. 104 out of 140 employees were recruited as participants using a purposive sampling technique based on several criteria. The obtained data are considered representative of the population. This study examined the effect of workmotivation, work discipline, and compensation on employee performance. These variables were analyzed the Work from Home (WFH) setting during the COVID-19 pandemic. The result of the study may provide a positive recommendation to improve employee performance when working from home. This study found that work motivation and discipline positively affected employees’ job performance. Compensation did not affect but had a positive relationship with employees’ job performance. Work discipline was found to be the most dominant variable affecting the increase in employee performance during WFH. The organization needs to evaluate the compensation program to improve the work outcome quality and rewards for employees during the WFH program.